2002
DOI: 10.1111/j.1572-0241.2002.05836.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of Crohn's disease activity: a comparison of 18F-fluorodeoxyglucose positron emission tomography, hydromagnetic resonance imaging, and granulocyte scintigraphy with labeled antibodies

Abstract: FDG-PET appears to be a reliable noninvasive tool for simultaneous detection of inflamed areas in the small and large bowel of patients with CD. FDG-PET can be used to detect disease activity in the terminal ileum and colon of CD patients with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(51 citation statements)
references
References 25 publications
0
48
0
3
Order By: Relevance
“…FDG-PET depicts cells with an enhanced glucose metabolism. Apart from its role in the evaluation of malignancies, the role of FDG-PET in the diagnosis of focal inflammation and infection has been studied in patients suffering from osteomyelitis [1–3], vasculitis [48], inflammatory bowel disease [911] and sarcoidosis [12, 13]. Moreover, recent studies have shown its usefulness as a diagnostic tool in patients with fever of unknown origin (FUO) where more than one third of the PET scans were considered helpful in reaching a final diagnosis [1417].…”
Section: Introductionmentioning
confidence: 99%
“…FDG-PET depicts cells with an enhanced glucose metabolism. Apart from its role in the evaluation of malignancies, the role of FDG-PET in the diagnosis of focal inflammation and infection has been studied in patients suffering from osteomyelitis [1–3], vasculitis [48], inflammatory bowel disease [911] and sarcoidosis [12, 13]. Moreover, recent studies have shown its usefulness as a diagnostic tool in patients with fever of unknown origin (FUO) where more than one third of the PET scans were considered helpful in reaching a final diagnosis [1417].…”
Section: Introductionmentioning
confidence: 99%
“…SPECT tracers: Neurath et al[53] enrolled 59 patients with CD in a prospective study, in order to assess disease activity by FDG-PET, hydro-MRI, and immunoscintigraphy with anti-nonspecific cross-reacting antigen 95 antigranulocyte antibodies. Twelve patients with irritable bowel syndrome and 20 patients with gut cancer but without gut inflammation served as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have indicated the potential of FDG-PET to assess CD activity [1315], although to our knowledge, there is no report on its potential to assess CD-associated malignant tumors. We performed FDG-PET in four of our patients prior to surgery and the results were positive in two patients and negative in two [16].…”
Section: Discussionmentioning
confidence: 99%